Faktor-faktor yang Berhubungan dengan Kecemasan Keluarga Dimasa Pandemi Covid-19 di Wilayah Kerja Puskesmas Sukarame Kota Palembang Tahun 2021 - Rice Hernanda; Budi Mulyadi; Siti Yuliharni (Universitas Batanghari Jambi, 2022)
This study aims to determine the factors associated with family anxiety during the COVID-19 pandemic in the Sukarame work area, Palembang City. The research method used is quantitative research with a cross-sectional approach. The study was conducted in August with a sample of 206 respondents. The research instrument was in the form of a questionnaire and then analyzed the multivariate logistic regression Odd Ratio data. The results showed that education, knowledge, attitudes, health services and support from community leaders had a significant relationship with family anxiety during the COVID 19 pandemic at the Sukarame Public Health Center in 2021. All factors indicated health services as the dominant factor associated with family anxiety levels in the community. health services with an OR value of 3.867. The opportunities for family anxiety experienced by education, knowledge, attitudes, health services and support from community leaders are only 27.1%, the rest 72.9% are other factors outside of this study.